Sistem Pendukung Keputusan Pemilihan Karyawan Berprestasi Menerapkan Metode Vise Kriterijumska Optimizajica I Kompromisno Resenje (VIKOR) - Trisnani, Anis A; Anwar, Dede Utari; Ramadhani, Wulan; Manurung, Monica M; Siahaan, Andysah Putera Utama (JURIKOM (Jurnal Riset Komputer), 2018)
The quality of human resources is one of the supporting factors to improve the productivity of a company's performance. Highly competent human resources can support the level of performance, with performance appraisal it will get the achievements achieved by each employee. To obtain fast and accurate information the employee's exact accomplishment meets the expected criteria. To find that out, with a multicriteria decision-making method by solving complex and unstructured situations into sections and compiling them using the Vise Kriterijumska Optimizajica I Kompromisno Resenje (VIKOR) method on Decision Support System (SPK), the determination of achieving employees can be calculated based on calculation of the weight of each criterion, so it can select employees achievers in the company quickly